Authorial voices and minority realities: South Indian Muslim women's narratives - Rahmath, Hayshath Shamah; Raihanah, M. M. (Penerbit Universiti Kebangsaan Malaysia, 2025)
This research paper examines the narratives of South Indian Muslim women writers across three distinct waves: the first wave (late 19th to early 20th century), the second wave (mid to late 20th century), and the third wave (21st century). It explores how these writers articulate their experiences and social realities within the minority contexts of South India, utilising W.E.B. Du Bois' concept of "double consciousness" to analyse the internal conflicts faced by Muslim women. The study further expands upon this framework through the concept of "subjugated consciousness," as adapted by Joe L. Kincheloe and Shirley R. Steinberg, which highlights the significance of women's subordinated knowledge in understanding their responses to oppression. Additionally, the research incorporates the notion of "authorially defined social reality," as articulated by Raihanah M. M., to examine how these writers construct their social realities through their narratives. Using a qualitative, thematic textual analysis grounded in critical theory, this paper investigates the works of notable authors such as P.K. Haleema, Haleema Beevi, Sara Aboobacker, Banu Mushtaq, Khadija Mumthas, Rajathi Salma, and Andaleeb Wajid, reflecting the interplay of cultural, religious, and gendered dynamics. Key themes such as education, social justice, identity, and resistance are identified, providing insights into the socio-political landscape affecting Muslim women in South India. By emphasising the significance of authorial voices in shaping minority narratives, this paper contributes to a deeper understanding of the lived experiences of South Indian Muslim women and their assertions of agency within a complex environment.